Identifikasi Akuifer Air Tanah dengan Vertical Electrical Sounding (VES) Berdasarkan Kondisi Geologi di Daerah Bulalo, Gorontalo Utara - Moh. Syach L. Lasahido; Ahmad Zainuri; Noviar Akase (Universitas Negeri Gorontalo, 2025)
This study aims to identify and understand the geological characteristics and groundwater aquifer potential in the study area. The research methods employed include surface geological mapping, borehole data interpretation, as well as lithology and structural geology analysis. The results indicate that the geological formations in the study area are predominantly composed of sedimentary and volcanic rocks with significant lithological variations, such as sandstone, claystone, and tuff. The identified geological structures, including folds and faults, influence the distribution of aquifers and groundwater flow. Aquifers in the study area are categorized into unconfined and confined aquifers, with the highest potential found in sandstone layers due to their high porosity and permeability. These findings are expected to serve as an important foundation for the sustainable management of groundwater resources in the study area.